Surface enhanced Raman spectroscopic studies on the adsorption behaviour of nitric oxide on a Ru covered Au nanoparticle film. Issue 21 (26th March 2020) - Ge, Ming; Wu, Qian; Yin, Lu; Xu, Minmin; Yuan, Yaxian; Guo, Qinghua; Yao, Jianlin
Abstract : A SERS borrowing strategy with well-designed substrates has been developed to monitor the adsorption and dissociation of NO at Au/Ru surfaces. Abstract : Nitric oxide (NO) is very interesting because of its effects on air pollution and especially biological systems. The adsorption behavior of NO molecules has fundamental importance with great technical challenges due to complex processes and species identification. Herein, the NO adsorption behavior on a Ru surface has been investigated using well-designed surface enhanced Raman spectroscopy (SERS) substrates. A Au nanoparticle monolayer film on ITO was employed as the electrode and Ru layers were electrochemically deposited. The internal SERS effect from the Au nanoparticles with high sensitivity and the metallic surfaces of Ru with practical application were integrated into a composite Au/Ru substrate. The molecular adsorption and dissociation of NO were observed simultaneously by SERS. A competitive relationship between adsorption and dissociation was observed at higher NO pressure, and the 3-fold and 2-fold bridge and top adsorption configurations appeared on the surface and were associated with different ν NO vibrational frequencies. The results indicated that 3-fold bridge sites are preferred for dissociation over other structures. The dissociation of NO produced adsorbed atomic nitrogen and oxygen species to form Ru–N and Ru–O bonds, respectively. The dissociation process, especially for linear NO, was site dependent and blocked at higher pressure or coverage. Due to the change in adsorption energy and coverage, a conversion of the adsorption configuration from bridge to top was observed in the initial stage of NO adsorption, and this was followed by a mixture of bridge and top configurations of NO and dissociated species. A two-step dissociation mechanism and the steps of NO adsorption were proposed. The present study suggested that the SERS technique with appropriate attractive metal overlayers provided a significant and possibly even a valuable approach to explore adsorption behavior and kinetics at gas–solid interfaces.